2023
DOI: 10.3390/infrastructures8020029
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Stress Modeling of Resilient Modulus in Sandy Subgrade Soils

Abstract: The mechanical properties of pavement materials are crucial to the design and performance of flexible pavements. One of the most commonly used measures of these properties is the resilient modulus (Er). Many different models were developed to predict the resilient modulus of coarse soils, which are based on the states of stresses and the physical and mechanical properties of the soil. The unconsolidated unsaturated drained cyclic triaxial tests were performed for three variously graded and three well-graded sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Seed, Mitry, Monismith, and Chan [19] found that the stress variables (e.g., bulk stress, deviator stress, and octahedral stress) significantly affect the resilient modulus. Several models have been built to predict the resilient modulus of subgrade soils using bulk stress, deviatoric stress, or a combination [20][21][22][23][24][25]. The bulk stress, which includes Geotechnics 2023, 3 361 the confining pressure and deviator stress, is used by most resilient-modulus prediction models.…”
Section: Introductionmentioning
confidence: 99%
“…Seed, Mitry, Monismith, and Chan [19] found that the stress variables (e.g., bulk stress, deviator stress, and octahedral stress) significantly affect the resilient modulus. Several models have been built to predict the resilient modulus of subgrade soils using bulk stress, deviatoric stress, or a combination [20][21][22][23][24][25]. The bulk stress, which includes Geotechnics 2023, 3 361 the confining pressure and deviator stress, is used by most resilient-modulus prediction models.…”
Section: Introductionmentioning
confidence: 99%